Stolen magic - Levine, Gail Carson (New York : Harper, 2015)
Elodie, the dragon detective Meenore, and the kindly ogre Count Jonty Um are all on their way to Elodie's home island of Lahnt. Elodie has barely set foot on land before she learns that the Replica, a statue that keeps her island's deadly volcano from erupting, has been stolen! If the Replica isn't found in three days, a mountain will be destroyed. And when Elodie ends up alone with a cast of characters each of whom may be guilty, she has to use her wits to try to unravel a tangled web of lies.
Ages 8-12.
Keywords: Apprentices -- Juvenile fiction; Dragons -- Juvenile fiction; Fantasy fiction